2012
DOI: 10.15288/jsad.2012.73.268
|View full text |Cite
|
Sign up to set email alerts
|

Husband and Wife Alcohol Use as Independent or Interactive Predictors of Intimate Partner Violence

Abstract: ABSTRACT. Objective: Men's heavy drinking has been established as a risk factor for their perpetration of intimate partner violence (IPV); however, the role of women's drinking in their perpetration of IPV is less clear. The current study examined the relative strength of husbands' and wives' alcohol use and alcohol dependence symptoms on the occurrence and frequency of husbands' and wives' IPV perpetration. Method: Married and cohabiting community couples (N = 280) were identifi ed and recruited according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 41 publications
10
64
1
Order By: Relevance
“…It was more common for only one partner to report that IPA had occurred. Consistent with survey research (e.g., Testa et al, 2012) and our previous analyses from this sample , uncorroborated reports of both victimization and perpetration were generally more likely to be reported by the female than by the male partner, according to McNemar's test.…”
Section: Hourly Reports Of Ipasupporting
confidence: 88%
See 1 more Smart Citation
“…It was more common for only one partner to report that IPA had occurred. Consistent with survey research (e.g., Testa et al, 2012) and our previous analyses from this sample , uncorroborated reports of both victimization and perpetration were generally more likely to be reported by the female than by the male partner, according to McNemar's test.…”
Section: Hourly Reports Of Ipasupporting
confidence: 88%
“…Examining the association between IPA and alcohol use is complicated by the surprisingly low agreement between relationship partners regarding the occurrence of IPA (Caetano et al, 2009;Schafer et al, 2002;Testa et al, 2012). For example, one partner may report an episode of IPA in which she both perpetrated and experienced victimization; however, her partner may report only perpetration, only victimization, or neither.…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…30 Additionally, male-to-female IPV perpetration has been consistently linked to heavy drinking by men 31 and AUD. 32,33 It is relevant to highlight that gender differences were not spotted with regards to perpetration of violence in our results. We also found that major predictors of IPV perpetration, such as illegal substance use (apart from sedative use), were identical between genders.…”
Section: Discussionmentioning
confidence: 75%
“…It is likely that any characteristic that increases people’s sensitivity to negative partner behavior will increase the likelihood that such behavior is seen as aggressive. For example, women report both more victimization and perpetration than is corroborated by their partner (e.g., Testa & Derrick, 2014; Testa et al, 2012). Similarly, people with lower relationship satisfaction report receiving more psychological aggression than their partner reports perpetrating (Marshall, Panuzio, Makin-Byrd, Taft, & Holtzworth-Munroe, 2011).…”
Section: Hypothesesmentioning
confidence: 99%